Pengaruh Rasio Keuangan dan Makro Ekonomi terhadap Harga Saham pada Perusahaan Sektor Consumer Goods di BEI - Dhira Maulana (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research examines the relation of financial ratio and macroeconomics to stock price. The financial ratios used in this research are the return on assets (ROA), debt to assets ratio (DAR), debt to equity ratio (DER), dan price earning ratio (PER). However, the macroeconomy uses inflation, Bank Indonesia rate, and exchange rate. The research sample uses secondary data such as annual reporting from consumer goods companies listed in Indonesia Stock Exchange (IDX). Twenty-eight companies were used as a sample in this research, using the purposive sampling technique. This research uses multiple regression analysis and uses SPSS 24.0 as a tool. This research shows that ROA, PER, and inflation had no significant influence on the stock price. On the other hand, DAR, DER, Bank Indonesia rate, and exchange rate significantly influenced the stock price. ROA does not have a significant influence on stock price can be caused by investors' view that ROA can be changed not only driven by corporate profits but can also be caused by the changes of corporate assets. So the decline in ROA does not always reflect a decrease in corporate profits but can be caused by an increase in corporate investments. PER does not have a significant influence on stock price can be caused by the high level of investor confidence in the prospects of consumer goods sector companies because the consumer goods sector contains companies that produce consumption needs. While inflation does not have a significant influence on stock price can be caused by the view of investors that inflation in the long term will not endanger the funds of investors who are in the capital market.